The role of peer influences on the normalisation of sports wagering: a qualitative study of Australian men - Deans, E.; Thomas, S.; Daube, Mike; Derevensky, J. (Informa Healthcare, 2017)
Sports wagering has been identified as a gambling product which may pose particular risks for young men, because of the aggressive marketing tactics used to promote these products, and the alignment with culturally valued sporting activities. However, there is very limited information about the socio-cultural processes that may contribute to the normalisation of sports wagering for this population. Using semi-structured interviews with 50 Australian young men who gambled on sport, we explored the way in which peer group behaviours influenced attitudes towards, and the consumption of, gambling products. Four thematic clusters emerged from the interviews. First, young men perceived that sports wagering was a ‘normal’ and socially accepted activity, and a natural ‘add on’ to sports. Second, there were clear indicators that sports wagering was becoming embedded within existing peer based sporting rituals, with the emergence of gambling clubs, and online forums. The third finding related to the shaping of gambling/sport discussions, which created a sense of identity and a point of conversation for peers. Finally, some participants spoke of the social pressure to gamble to ‘fit in’ with their friends. This study suggests that sports wagering poses a new health threat for young men, with sports wagering quickly being normalised as an embedded activity in young male sports fans' peer groups. There are clear lessons from the Australian experience for other countries, relating to the ways in which industry marketing tactics may combine with culturally valued activities such as sport, to influence risky gambling behaviours.